Potensi Zakat dalam Upaya Mengentaskan Kemiskinan - Kurnia Jaya, Toni (JURNAL ILMIAH GEMA PERENCANA, 2022)
The potential of zakat in efforts to alleviate poverty. Base on law number 23/2011, zakat is a potential source of funds for alleviating poverty. Zakat can function as working capital for the poor to be able to open jobs and entrepreneurship. Zakat does not eliminate the government's obligation to create welfare but only helps part of this government's responsibility to the community through the National Amil Zakat Agency (BAZNAS). The purpose of this writing is to explain the importance of empowering zakat in an effort to alleviate poverty. The distribution of productive zakat will not only raise the standard of living of the poor because they are already able to start their own business, it will also leverage the economy to be able to absorb local workers (reduce unemployment) and contribute to increasing economic growth. The method in this writing is analytical descriptive, which seeks to provide a clear picture of the main issues that exist, namely by methodologically analyzing the poor who receive zakat from BAZNAS. The Amil Zakat Institution is expected to be able to optimize muzakki data through the zakat data bank so that it can be more optimal in collecting zakat, as well as mapping zakat recipients and potential mustahik who have the ability to manage zakat to apply productive zakat distribution to people who will receive zakat. With the provision of zakat funds carried out by BAZNAS to the poor or those in need, it is very useful and the community really feels the benefits.